2011
DOI: 10.1186/1742-2094-8-38
|View full text |Cite
|
Sign up to set email alerts
|

Specific PKC isoforms regulate LPS-stimulated iNOS induction in murine microglial cells

Abstract: BackgroundExcessive production of nitric oxide (NO) by inducible nitric oxide synthase (iNOS) in reactive microglia is a major contributor to initiation/exacerbation of inflammatory and degenerative neurological diseases. Previous studies have indicated that activation of protein kinase C (PKC) can lead to iNOS induction. Because of the existence of various PKC isoforms and the ambiguous specificity of PKC inhibitors, it is unclear whether all PKC isoforms or a specific subset are involved in the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 49 publications
(52 reference statements)
5
38
0
Order By: Relevance
“…In particular, we can suppose that PKC might act as an upstream regulator of NF-κB, STAT1 and CREB. The hypothesis of the activation of the PKC/NF-κB pathway following NO donors' administration, that contributes to the induction of allodynia/hyperalgesia, was confirmed by studies conducted on murine microglia showing that LPS-and peptidoglycan-induced iNOS production appears to be mediated by a signaling pathway involving the sequential of PKC and NF-κB activation (Bhatt et al 2010;Wen et al 2011). Similarly, we can suppose that PKC might be involved in the NO-induced supraspinal activation of STAT1.…”
Section: Discussionmentioning
confidence: 65%
“…In particular, we can suppose that PKC might act as an upstream regulator of NF-κB, STAT1 and CREB. The hypothesis of the activation of the PKC/NF-κB pathway following NO donors' administration, that contributes to the induction of allodynia/hyperalgesia, was confirmed by studies conducted on murine microglia showing that LPS-and peptidoglycan-induced iNOS production appears to be mediated by a signaling pathway involving the sequential of PKC and NF-κB activation (Bhatt et al 2010;Wen et al 2011). Similarly, we can suppose that PKC might be involved in the NO-induced supraspinal activation of STAT1.…”
Section: Discussionmentioning
confidence: 65%
“…8 A, lanes 1-3). To confirm these observations, primary microglia were treated with LPS, which causes robust microglia activation and iNOS upregulation (Sheng et al, 2011;Wen et al, 2011). LPS treatment led to a significant increase in iNOS expression in untransduced cells and considerably enhanced the upregulation of iNOS caused by adenovirus infection (Fig.…”
Section: Runx1 Inhibits Microglia Activation In Vitromentioning
confidence: 99%
“…LPS-activated microglia are known to express iNOS and release NO (Kumar et al, 2014;Wen et al, 2011). We therefore tested whether blocking iNOS with the specific inhibitor N-(3-(aminomethyl)benzyl)acetamidine dihydrochloride (1400 W) prevented uptake of live PC12 cells, and found that it partially inhibited this phagocytosis (Fig.…”
Section: No From Microglia Induces Ptdser Exposure On Pc12 Cells and mentioning
confidence: 99%